Car exhaust waste heat recovery using hexagon shaped thermoelectric generator / Muhammad Fairuz Remeli, Baljit Singh and Aiman Ismail - Remeli, Muhammad Fairuz; Singh, Baljit; Ismail, Aiman (Smart Manufacturing Research Institute (SMRI), 2021)
Heat recovery technology using thermoelectric has attracted many research intentions mainly for its ability to generate power passively. The automotive engine usually produces waste heat ranging from 30-40% due to the thermodynamic limit. The use of thermoelectric generator (TEG) for waste heat recovery and power generation could increase the efficiency of the internal combustion engine system. This research developed and investigated a heat recovery system using a thermoelectric generator (TEG) for power generation. A thermoelectric generator (TEG) consisted of thermoelectric modules, hexagonal pipe connector and heat sinks was built and connected to an exhaust pipeline. A theoretical model was developed to access the thermal and electrical performance of the TEG system. The theoretical model consisted of the heat transfer mechanism including the thermal resistance networks from the flue gas to TEG and the heat sink. The electrical power output was determined using the Seebeck principle. The early stage of finding reveals that the system was able to produce an open circuit voltage of 0.13 V for a small temperature gradient of 3ᵒC between the cold and hot surface of the TEG. The further improvement of the system is currently under investigation for producing higher power. In the future, this system hopefully could replace the car battery for charging the alternator as well as increasing the overall efficiency of the engine system.